Site Analysis of Kolam Evu for Sustainable Tourism Development - Apolinaris Remetwa; Darmansjah Tjahja Prakasa; Suko Istijanto (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Kolam Evu is a natural tourism area located on Kei Kecil Island with distinctive characteristics, including natural spring water, high water clarity, and strong local cultural values. This study aims to analyze site conditions as a basis for sustainable tourism development. The research employs a qualitative descriptive method through field observation, literature review, and spatial analysis (Creswell & Creswell, 2018). The findings indicate that Kolam Evu has strong potential to be developed using a contextual architectural approach while maintaining environmental sustainability (UNWTO, 2021). Development strategies include zoning, circulation planning, and the use of local materials. This study contributes as a reference for sustainable tourism planning (UNWTO, 2021).